Topical Aloe Vera as an Adjunctive Therapy for Diabetic Foot Ulcers: A Systematic Review - Syafiq Maulana (Majalah Kesehatan Indonesia, 2026)
Diabetic foot ulcers (DFUs) remain a persistent clinical challenge due to impaired healing and high infection risk. This systematic review evaluates the potential benefit of topical Aloe vera as an adjunct to standard DFU care. A structured search of PubMed, ScienceDirect, ProQuest, and Google Scholar was conducted up to December 30, 2025, following PRISMA 2020 guidelines. Eight clinical studies (six randomized controlled trials/RCTs and two quasi-experimental studies), involving 402 patients, were included. Outcomes assessed included BWAT/BJWAT scores, granulation, epithelialization, and ulcer size. Across studies, Aloe vera was associated with improvements in wound healing parameters, particularly in mild-to-moderate, non-ischemic ulcers during early healing phases. Risk of bias assessment showed generally low to moderate concerns among RCTs, while non-randomized studies presented serious to critical risk of bias. Using GRADE, the certainty of evidence was low for wound scores and ulcer size reduction, and very low for granulation and healing outcomes, mainly due to risk of bias, inconsistency, and imprecision. Overall, Aloe vera may provide some benefit as a low-cost adjunctive therapy; however, the current evidence remains limited and should be interpreted with caution. Further well-designed, adequately powered trials with standardized outcomes are needed.